2009
DOI: 10.1056/nejmoa0900043
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative Staging of Lung Cancer with Combined PET–CT

Abstract: The use of PET-CT for preoperative staging of NSCLC reduced both the total number of thoracotomies and the number of futile thoracotomies but did not affect overall mortality. (ClinicalTrials.gov number, NCT00867412.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
244
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(276 citation statements)
references
References 14 publications
7
244
0
12
Order By: Relevance
“…Even with the best currently available noninvasive staging tests, almost one in every three thoracotomies may be futile [19]. Thus, invasive methods have a vital role in mediastinal staging of NSCLC.…”
Section: Invasive Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even with the best currently available noninvasive staging tests, almost one in every three thoracotomies may be futile [19]. Thus, invasive methods have a vital role in mediastinal staging of NSCLC.…”
Section: Invasive Methodsmentioning
confidence: 99%
“…Another recent randomized Canadian trial of 337 patients by Maziak and colleagues comparing PET-CT with conventional staging (CT abdomen and bone scan) in suspected early stage NSCLC on routine CT (all patients also had brain CT or MRI) demonstrated that PET-CT correctly upstaged disease in 13.8% of patients as compared with only 6.8% in conventional staging group (p = 0.046) and prevented unnecessary thoracotomies [20]. In this context, it is important to note that studies of PET-CT have not clearly shown any improvement in mortality in NSCLC [19,20] and the issue of cost-effectiveness is still not fully clear. In spite of its pros and cons, PET-CT has been overwhelmingly adopted by the medical community and is recommended by current guidelines in the initial evaluation of all NSCLC patients [9,12].…”
Section: Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated PET-CT also decreased futile thoracotomies similar to PET alone: 52% in the conventional staging group to 35% in the group with PET-CT (P ¼ 0.05; ref. 15). For every 5 PET-CTs performed, 1 futile thoracotomy is avoided; however, this does not result in survival difference.…”
Section: Stagingmentioning
confidence: 99%
“…In the same study collective, the authors recently assessed the effect of combined PET/CT imaging on preoperative staging of NSCLC [5]. The number of patients identified as having advanced disease is twice as high as compared to the conventional group and, subsequently, a significantly higher number of non-curative, thus, unnecessary surgical A. K. Buck (*)interventions were performed in the conventional staging group.…”
mentioning
confidence: 99%